2022
DOI: 10.1136/bmjopen-2021-058768
|View full text |Cite
|
Sign up to set email alerts
|

Sacrifice and solidarity: a qualitative study of family experiences of death and bereavement in critical care settings during the pandemic

Abstract: BackgroundPandemic-related restrictions are expected to continue to shape end-of-life care and impact the experiences of dying hospitalised patients and their families.ObjectiveTo understand families’ experiences of loss and bereavement during and after the death of their loved one amidst the SARS-CoV-2 (COVID-19) pandemic.DesignQualitative descriptive study.SettingThree acute care units in a Canadian tertiary care hospital.ParticipantsFamily members of 28 hospitalised patients who died from March–July 2020.Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
1
13
0
3
Order By: Relevance
“…Furthermore, in the UK, while many ICUs conducted virtual visits for all patients, some only facilitated virtual visiting during end of life or acute deterioration, others only facilitated virtual visits in awake and stable patients [ 9 ]. Infrequent anger following a virtual visit may be reflective of an attitude of acquiescence also demonstrated in a Canadian study of family members bereaved during the pandemic [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the UK, while many ICUs conducted virtual visits for all patients, some only facilitated virtual visiting during end of life or acute deterioration, others only facilitated virtual visits in awake and stable patients [ 9 ]. Infrequent anger following a virtual visit may be reflective of an attitude of acquiescence also demonstrated in a Canadian study of family members bereaved during the pandemic [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining bereavement during the pandemic have found that prolonged and complex grief is common ( Dennis et al, 2022 ; Torrens-Burton et al, 2022 ). Importantly, these reactions have been linked to particular experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these reactions have been linked to particular experiences. Twenty-eight interviews with family members conducted on average 9 months after bereavement due to COVID-19 death in intensive care units emphasised the importance of communication and visitation ( Dennis et al, 2022 ). The inability to visit the dying and restricted funeral and after death rituals has been associated with feelings of anger, guilt and lack of acceptance of death ( Torrens-Burton et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the significance of connectedness at the end of life [33], and the present additional stressors caused by the pandemic circumstances, the negative effects of constrained connections between patients and family caregivers must not be neglected. These include the increased burden and stress-related symptoms [34], decreased quality of communication with healthcare professionals [17], compromised dignity [35], and long-lasting grief [36]. For family caregivers, double-hit effects of the pandemic, due to the risk of contagion and risk of social isolation, have been reported [37].…”
Section: Pandemic-dependent Palliative Care Needsmentioning
confidence: 99%